The interventional effect of astragaloside IV on rodent models of myocardial fibrosis: a systematic review and meta-analysis - Li, Haozhe; Chu, Yunhang; Wang, Yue; Wang, Yuan; Zhang, Yebo (Frontiers in Pharmacology, 2025)
ObjectiveThis study was conducted to evaluate the interventional effects of astragaloside in a rodent model of myocardial fibrosis (MF).MethodsData from studies related to the intervention of astragaloside IV (AS-IV) in rodent models with myocardial fibrosis were systematically retrieved and extracted. The outcome indices included collagen volume fraction (CVF), left ventricular end-systolic diameter (LVESd), left ventricular end-diastolic diameter (LVEDd), interventricular septal thickness at diastole (IVSd), left ventricular posterior wall diastolic thickness (LVPWd), left ventricular internal diameter at diastole (LVIDd), left ventricular mass index (LVMI), left ventricular fractional shortening (LVFS), left ventricular end-diastolic pressure (LVEDp), left ventricular systolic pressure (LVSP), left ventricular internal diameter at systole (LVIDs), left ventricular ejection fraction (LVEF), maximum rate of systolic pressure rise (+dp/dtmax), maximum rate of diastolic pressure fall (−dp/dtmax), and other hemodynamic indices. Additionally, it included lactate dehydrogenase (LDH), tumor necrosis factor-alpha (TNF-α), body weight (BW), and heart rate (HR). The methodological quality of the studies was assessed using the SYRCLE risk of bias tool, and these results were statistically analyzed by meta-analysis. Additionally, meta-regression and subgroup analyses were performed according to species, administration dosage, and administration duration, aiming to further deepen the understanding of the study results and provide references for relevant clinical research.ResultsA total of 38 studies were incorporated into the meta-analysis. The findings indicated that AS-IV led to a reduction in morphostructural indices, including CVF, LVESd, LVEDd, IVSd, LVPWd, and LVMI. Moreover, it decreased LVEDp and LVSP, while increasing hemodynamic indices such as LVEF, LVFS, +dp/dtmax, and −dp/dtmax. Additionally, astragaloside decreased biochemical and physiological indices, including LDH, TNF-α, HR, and BW. However, it exerted no significant impact on the levels of LVIDs and LVIDd in the model.ConclusionAS-IV can be used as a supportive treatment for MF, acting through various mechanisms, including the relief of inflammation, myocardial injury, and oxidative stress, thereby contributing to the improvement of ventricular diastolic and contractile capacity and reducing the necrosis and apoptosis of cardiomyocytes.Systematic Reviewhttps://www.crd.york.ac.uk/PROSPERO/myprospero, identifer CRD420250637182.